One-Day Prevalence of Extended-Spectrum β-Lactamase (ESBL) and Carbapenemase-Producing Bacteria in Fecal Samples from Surgical Patients: A Concerning Trend of Antibiotic Resistance - Sintondji K; Lègba B; Koudokpon CH; Fabiyi K; Dougnon V (Infection and Drug Resistance, 2025)
Kevin Sintondji, Boris Lègba, Charles Hornel Koudokpon, Kafayath Fabiyi, Victorien Dougnon Research Unit in Applied Microbiology and Pharmacology of Natural Substances, Research Laboratory in Applied Biology, Polytechnic School of Abomey-Calavi, University of Abomey-Calavi, Cotonou, BeninCorrespondence: Victorien Dougnon, Research Unit in Applied Microbiology and Pharmacology of natural substances, Research Laboratory in Applied Biology, Polytechnic School of Abomey-Calavi, University of Abomey-Calavi, 01 P.O. Box 2009, Cotonou, Benin, Tel + 229 01 97 73 64 46, Email victorien.dougnon@gmail.comPurpose: Extended-spectrum β-lactamase (ESBL) and carbapenemase producing bacteria are of increasing concern due to their multidrug resistance and infection potential. This study determines the one-day prevalence of faecal carriage of ESBL and carbapenemase producing Gram-negative bacilli.Methods: Fecal samples were collected from 30 post-surgery patients (hospitalized for at least 48 hours) in each of the four hospitals involved in the study and were analyzed for antibiotic-resistant bacteria. Identification was done using Maldi Tof mass spectrometry, and antibiotic susceptibility was tested using disk diffusion and specialized tests for ESBL (double disk synergy technique) and carbapenem (NG-TEST CARBA 5) resistance detection. PCR was conducted on isolates to detect betalactam resistance genes, carbapenemase genes and quinolone resistance genes.Findings: Out of the 120 patients enrolled, 38.33% (n = 46) and 49.16.33% (n = 59) were found to carry ESBL- and carbapenemase-producing bacteria, respectively, in their fecal samples. Among the isolates, 51.08% (n = 47) exhibited ESBL production, with Escherichia coli (44.56%) being the most common species. The identification of bacteria with resistance to carbapenems showed a predominance of the species Escherichia coli (44.45%) followed by the species Klebsiella pneumoniae (16.06%) and Acinetobacter baumanii (13.58%). The study of the association of variables shows a high degree of association (p < 0.05) for the factors independent walking and use of a wheelchair with ESBL production. The most frequently detected genes among ESBL producing bacteria were blaCTXM-1 (91.49%), qnrB (70.21%) and qnrs (63.82%). blaNDM (54.68%) was the most detected carbapenemase genes among carbapenemase producing isolates.Conclusion: This study demonstrates, for the first time, a significant prevalence of ESBL and carbapenemase producing gram-negative bacteria among surgical patients in Benin, with multiple resistance genes detected. Findings should be interpreted in light of the cross-sectional design and > 48-hour hospitalization criterion.Keywords: ESBL, carbapenemase, fecal carriage, post-surgery patients, one-day prevalence